Clypeal excision in Tapinoma Förster, 1850 ants is adaptive (Hymenoptera: Formicidae). - Seifert, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Evidence is presented that the median clypeal excision in the dolichoderine ant genus Tapinoma Förster, 1850 is a rare adaptive trait improving the protrusion of mouthparts for better exploitation of food or water sources located in narrow cleft spaces. The problem of getting access to food from, for example, narrow tubes of nectaries becomes more serious with increasing worker head width. A regression analysis of species-specific means in 16 Westpalaearctic Tapinoma species shows that the relative depth of clypeal excision grows significantly with head width in the interspecific comparison (p